Ca2Ga4Ge6 and Ca3Ga4Ge6: Synthesis, Structure, and Electronic Properties. Issue 15 (4th February 2022) - Hodge, Kelsey L.; Davis, H. Olivia; Koster, Karl G.; Windl, Wolfgang; Moore, Curtis E.; Goldberger, Joshua E.
Abstract: During the search for transition metal‐free alkyne hydrogenation catalysts, two new ternary Ca−Ga−Ge phases, Ca2 Ga4 Ge6 ( Cmc 21, a=4.1600(10) Å, b=23.283(5) Å, c=10.789(3) Å) and Ca3 Ga4 Ge6 ( C 2/ m, a=24.063(2) Å, b=4.1987(4) Å, c=10.9794(9) Å, β=91.409(4)°), were discovered. These compounds are isostructural to the previously established Yb2 Ga4 Ge6 and Yb3 Ga4 Ge6 analogues, and according to Zintl‐Klemm counting rules, consist of anionic [Ga4 Ge6 ] 4− and [Ga4 Ge6 ] 6− frameworks in which every Ga and Ge atom would have a formal octet with no Ga−Ga or Ga−Ge π‐bonding. These compounds are metallic, based on temperature dependent electrical resistivity and thermopower measurements for Ca3 Ga4 Ge6, along with density functional theory calculations for both phases. Unlike the highly active 13‐layer trigonal CaGaGe phase, these new compounds exhibit minimal activity in the semi/full alkyne hydrogenation of phenylacetylene, which is consistent with previous observations that the lack of a formal octet for framework atoms is essential for catalysis in these Zintl‐Klemm compounds. Abstract :